Smart home gardening system using internet of things (IOT) platforms - Ali, Rozita Binti Md; Abdullah, Afsal Binti (Southeast Asian Journal of Technology and Science, 2022)
In the current era of technological development, all human activities use information technology to facilitate all our daily activities. Among the activities that use the development of information technology is gardening activities at home and in the nursery.  Many people invest in gardening, but they fail to maintain it while on vacation or often forget to water the plants cause plants will wither and die.  The main objective of this system development is to facilitate farmers to manage and monitor their farms in an effective manner.  This system will be helping farmers to manage plants efficiently and effectively also makes it easier for farmers to water the plants with sufficient water based on the needs of the plants.  The scope is to produce a project through a sensor to detect soil moisture which is used as an indicator in the process of watering the trees and provide the ability to regulate soil moisture and control the watering process by using an automatic system to On/Off water in the tree watering process through mobile applications. This project was developed by using the Agile Model as a methodology.  Overall the development of IoT is beneficial in human life nowadays. As well as farmers running the country's agricultural industry, with a smart tree watering system, the watering process can be implemented in a timely and effective manner without wasting resources.